Detection, distribution, and functions of RNA N6-methyladenosine (m6A) in plant development and environmental signal responses - Xiang, Yang; Zhang, Dian; Li, Lei; Xue, Yi-Xuan; Zhang, Chao-Yang; Meng, Qing-Feng; Wang, Jin; Tan, Xiao-Li; Li, Yu-Long (Frontiers in Plant Science, 2024)
The epitranscriptomic mark N6-methyladenosine (m6A) is the most common type of messenger RNA (mRNA) post-transcriptional modification in eukaryotes. With the discovery of the demethylase FTO (FAT MASS AND OBESITY-ASSOCIATED PROTEIN) in Homo Sapiens, this modification has been proven to be dynamically reversible. With technological advances, research on m6A modification in plants also rapidly developed. m6A modification is widely distributed in plants, which is usually enriched near the stop codons and 3′-UTRs, and has conserved modification sequences. The related proteins of m6A modification mainly consist of three components: methyltransferases (writers), demethylases (erasers), and reading proteins (readers). m6A modification mainly regulates the growth and development of plants by modulating the RNA metabolic processes and playing an important role in their responses to environmental signals. In this review, we briefly outline the development of m6A modification detection techniques; comparatively analyze the distribution characteristics of m6A in plants; summarize the methyltransferases, demethylases, and binding proteins related to m6A; elaborate on how m6A modification functions in plant growth, development, and response to environmental signals; and provide a summary and outlook on the research of m6A in plants.